Design, synthesis, and herbicidal activity of indole-3-carboxylic acid derivatives as potential transport inhibitor response 1 antagonists - Wang, Xing; Luo, Mu-Jia; Wang, Yu-Xuan; Han, Wen-Qing; Miu, Jian-Xin; Luo, Xi-Ping; Zhang, Ai-Dong; Kuang, Yi (Frontiers in Chemistry, 2022)
Auxins as an important class of phytohormones play essential roles in a plant’s life cycle, therefore, developing compounds with auxin-like properties for plant growth regulation and weed control applications is of great significance. Herein, we report the design, synthesis, and herbicidal activity evaluation of a series of novel indole-3-carboxylic acid derivatives as auxin receptor protein TIR1 antagonists. Petri dish herbicidal activity assay demonstrated that most of the as-synthesized target compounds exhibited good to excellent inhibition effects (60~97% inhibitory rates) on roots and shoots of both dicotyledonous rape (B. napus) and monocotyledonous barnyard grass (E. cruss-galli). The inhibition rates of compounds 10d and 10h reach up to 96% and 95% for the root of rape (B. napus) at 100 mg/L, and they also maintain 92% and 93% inhibition rates even if at 10 mg/L, respectively. Molecular docking revealed that the interactions between these synthesized target compounds and TIR1 protein include tight π-π stacking, hydrogen bond and hydrophobic interactions. This work expands the range of auxin chemistry for the development of new auxin mimic herbicides.